Penerapan Metode Profile Matching pada Sistem Pendukung Keputusan Penentuan Karyawan Teladan - Sulistyohati, Aprilia; Muliyani, Nani; Riski, Muhammad (Journal Global Technology Computer, 2025)
The development of Industry 4.0 encourages companies to manage human resources (HR) more effectively, efficiently, and objectively, especially in the employee performance appraisal process. Manual assessments often face obstacles, such as subjectivity, inefficiency, and limitations in data processing. This study aims to develop a web-based Decision Support System (DSS) using the Profile Matching method to assist in the selection process of exemplary employees. The Profile Matching method is used to compare actual employee values with ideal profiles through the stages of GAP calculation, GAP weighting, determination of Core Factors (CF) and Secondary Factors (SF), and final ranking. The research was conducted through problem identification, literature study, determination of ideal criteria and weights, employee data collection, manual calculations, system development with UML and database design, web application implementation, as well as functional testing and result validation. Based on the test results, the system produces values and rankings that are consistent with manual calculations, proving that the applied algorithm runs correctly and in accordance with the profile matching method procedure. In addition, the system's ranking results are also in line with HRD evaluations, making the system suitable for use as a decision-making tool. Web-based implementation improves accessibility, efficiency, and transparency in data management. Overall, this research contributes to the use of information technology to improve the quality of employee performance management and support HR development strategies in the digital era.